ANALYSIS OF PHONOLOGICAL ERRORS IN FIRST SEMESTER STUDENTS IN PERFORMING SELF INTRODUCTION A CASE STUDY IN INSTITUTE LEVEL - Ni Made Ayu Purnami; Ni Made Ernila Junipisa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
Some problems have emerged related to the phonological errors made by the first semester students in delivering their speaking performance. This research is intended to analyze the phonological error in the first semester students in performing self-introduction. This study used qualitative research method particularly in terms of English phonology that focus on observing and analyzing the observation of English-speaking skill. In this research, the collected data were in the form of transcripts of the video-recorded performance that performed by the subjects of research. It is concluded that most students showed several phonological errors in pronouncing some words. All students of the first semester have successfully performed their self-introduction fluently and accurately based on the basic self-introduction pattern. The result of the study showed that the emergence of various variations in the accuracy of phonology is mainly due to the previous educational background and the students’ current efforts in learning language. However, most students of first semester did phonological errors in pronouncing several words. In order to speak English fluently and accurately, it is expected that the students learn about English phonology well by considering the appropriate place of articulation and manner of articulation.